Efficiency and contribution of strategies for finding randomized controlled trials: a case study from a systematic review on therapeutic interventions of chronic depression - Annika Westphal (Journal of Public Health Research, 2014)
Background. Identifying all existing evidence is a crucial aspect in conducting systematic reviews. Since the retrieval of electronic database searches alone is limited, guidelines recommend the use of addi- tional search strategies. The aim of this investigation was to assess the efficiency and contribution of additional search strategies for identifying randomized controlled trials in conducting a systematic review on interventions after performing a sensitive electronic database search. Design and Methods. Seven electronic databases, 3 journals and 11 systematic reviews were searched. All first authors of the included studies were contacted; citation tracking and a search in clinical trial registers were performed. A priori defined evaluation criteria were calculated for each search strategy. Results. A total of 358 full-text articles were identified; 50 studies were included in the systematic review, wherefrom 84.0% (42) were acquired by the sensitive electronic database search and 16.0% (8) through additional search strategies. Screening reference lists of related systematic reviews was the most beneficial additional search strategy, with an efficiency of 31.3% (5) and a contribution of 10.0% (5/50), whereas hand-searching and author contacts contributed two and one additional studies, respectively. Citation tracking and searching clinical trial registers did not lead to any further inclusion of primary studies. Conclusions. Based on our findings, hand-searching contents of relevant journals and screening reference lists of related systematic reviews may be helpful additional strategies to identify an extensive body of evidence. In case of limited resources, a sensitive electronic database search may constitute an appropriate alternative for identifying relevant trials.